Plantar pressure distribution in patients with ankylosing spondylitis. Issue 3 (March 2015) - Aydin, Elif; Turan, Yasemin; Tastaban, Engin; Kurt Omurlu, Imran; Sendur, Omer Faruk
Abstract: Background: Ankylosing spondylitis is one of the most common inflammatory rheumatic diseases and is associated with alterations in posture. The aim of this study was to investigate the pedobarographic changes among ankylosing spondylitis patients, in an attempt to understand whether the alterations in the posture affect the plantar pressure distribution. Methods: The study population consisted of 38 patients with ankylosing spondylitis and 33 healthy volunteers. The static and dynamic pedobarographic measurements were performed to determine the plantar pressure distribution. Moreover, the Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, Ankylosing Spondylitis Quality of Life Questionnaire and Bath Ankylosing Spondylitis Metrology Index were used to assess the clinical state of the patients. Results: The static pedobarographic measurements did not reveal any intergroup difference. There were differences between the groups in the results of dynamic peak pressure measurements under the metatarsal areas and under the midfoot region. The percentage of the midfoot in the dynamic plantar contact area was higher in ankylosing spondylitis patients in comparison to the controls. No clinically significant correlation was found between the clinical scores and static pedobarographic measurements. The plantar pressures under the metatarsal heads, medial and lateral heel regions declined with increasing disease activity according to the Bath Ankylosing Spondylitis Disease Activity Index scores. The lower peak pressures on the forefoot and rearfoot, were associated with the higher Bath Ankylosing Spondylitis Metrology Index scores of the patients. Interpretation: The alterations in the posture may have effects on the plantar pressures in patients with ankylosing spondylitis, especially during dynamic activities. Highlights: Static plantar pressure distribution was not different in ankylosing spondylitis. Pressures under forefoot and midfoot were higher during gait in ankylosing spondylitis. Lower pressures of forefoot and rearfoot were associated with higher clinical scores.